2020
DOI: 10.4039/tce.2020.50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nest microclimate temperatures on metabolic rates of small carpenter bees, Ceratina calcarata (Hymenoptera: Apidae)

Abstract: Small carpenter bees (Ceratina calcarata Robertson) (Hymenoptera: Apidae) build their nests in both sunny and shady sites, so maternal decisions about nest sites influence the thermal environment experienced by juveniles throughout development. A previous study demonstrated that when larvae and pupae were raised in the laboratory at room temperature, those from sunny nests developed more slowly than those from shady nests. This suggested that bees developing in sunny nests slowed their metabolism or that bees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…As expected, C. calcarata offspring exhibited higher metabolic rates (VCO 2 ) at 40°C than they did at 25°C, but sun and shade bees did not differ in their responses to temperature. The similarity in response contrasts with a previous study, in which bees from sunny nests showed elevated metabolic rates at 40°C (Richards et al 2020). Fieldwork for the previous study was carried out during the summer of 2016 which was one of the hottest, driest summers on record in southern Ontario, with temperatures slightly warmer than in 2020 (Supplementary Figure S2).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As expected, C. calcarata offspring exhibited higher metabolic rates (VCO 2 ) at 40°C than they did at 25°C, but sun and shade bees did not differ in their responses to temperature. The similarity in response contrasts with a previous study, in which bees from sunny nests showed elevated metabolic rates at 40°C (Richards et al 2020). Fieldwork for the previous study was carried out during the summer of 2016 which was one of the hottest, driest summers on record in southern Ontario, with temperatures slightly warmer than in 2020 (Supplementary Figure S2).…”
Section: Discussioncontrasting
confidence: 99%
“…The smaller size of sun offspring is at odds with the observation that sun and shade mothers exhibited similar rates of pollen foraging, which should have produced offspring of similar body sizes (Danforth 1990; Bosch and Vicens 2002). That sun offspring ended up smaller suggests that during development, they diverted energetic resources away from processes promoting growth and so ended up smaller (Atkinson 1994; Richards et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation can generally reduce surrounding temperature [ 64 ] and at an even finer scale, flowers including daffodils possess independent microclimates which, in some cases, act as warming pads for bees [ 77 ]. Shade produced by vegetation cover or other environmental factors can also influence the microclimates of nests used by cavity-nesting bees [ 78 ]. Such microclimate effects within the nest can influence the metabolic rate and development of bee larvae [ 78 , 79 ].…”
Section: Local Featuresmentioning
confidence: 99%
“…Shade produced by vegetation cover or other environmental factors can also influence the microclimates of nests used by cavity-nesting bees [ 78 ]. Such microclimate effects within the nest can influence the metabolic rate and development of bee larvae [ 78 , 79 ]. Abiotic factors i.e., nitrogen deposition, which is prevalent in urban areas, can interact synergistically with climate change in such a way that may influence local microclimates as well [ 7 , 80 ].…”
Section: Local Featuresmentioning
confidence: 99%